Fighting for Survival - Planning and Development Issues in two European Rural Border Mid-Mountain Regions - Sancho Reinoso, Alexis (Journal for Geography, 2010)
The main aim of this article (the paper is included in the context of a research project funded by the Spanish Ministry of Science and Technology – code: SEJ-2006-15331-C02-02) is to further our understanding of two mountain rural areas occupying two distinct geographical environments: the Spanish Pyrenees and the Austrian Alps. I am particularly interested in examining the management practices that have been adopted as part of the public policies implemented in two mid-mountain regions - areas that do not have the same possibilities for development as those enjoyed by high-mountain environments. These places suffer structural problems resulting from low levels of agricultural competitiveness, accompanied by factors that impinge negatively on land use (which, in turn, condition their landscape management practices). Finally, I reflect on the differences between the two regions and their future possibilities.